2015
DOI: 10.1097/wad.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Stenosis, Cerebrovascular Diseases, and Cognitive Impairment in Chinese

Abstract: Extracranial carotid artery disease has been shown to be related to cognitive deficits. However, limited data are available on intracranial stenosis (ICS) and cognitive impairment. We investigate the association between ICS and cognitive impairment in Chinese. Subjects (n=278), recruited from the Epidemiology of Dementia in Singapore Study, underwent comprehensive clinical evaluation, neuropsychological testing, and brain magnetic resonance imaging (MRI), including 3-dimensional-time-of-flight magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Additionally, potential mechanistic associations between GDF-15 and other putative biomarkers, such as brain natriuretic peptide, cardiac troponin-T, C-reactive protein, and markers of insulin resistance remain to be studied. [36,4648] Moreover, although we controlled for potential effects of NSAID medications on GDF-15 levels, other concurrently administered medications such as statins and proton-pump inhibitors may need to be considered as well, although in the case of statins, a previous study did not show any associations with GDF-15. [46] Lastly, while we have deliberately excluded VaD subjects in the present study due to our focus on markers of CeVD in AD, epidemiological studies have shown that at least a proportion of CIND with CeVD would go on to develop VaD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, potential mechanistic associations between GDF-15 and other putative biomarkers, such as brain natriuretic peptide, cardiac troponin-T, C-reactive protein, and markers of insulin resistance remain to be studied. [36,4648] Moreover, although we controlled for potential effects of NSAID medications on GDF-15 levels, other concurrently administered medications such as statins and proton-pump inhibitors may need to be considered as well, although in the case of statins, a previous study did not show any associations with GDF-15. [46] Lastly, while we have deliberately excluded VaD subjects in the present study due to our focus on markers of CeVD in AD, epidemiological studies have shown that at least a proportion of CIND with CeVD would go on to develop VaD.…”
Section: Discussionmentioning
confidence: 99%
“…CIND was determined by clinical judgment based on published guidelines, [36] namely, impairment in at least one domain of the neuropsychological test battery without any significant dysfunction in activities of daily living. Participants were considered to have failed a test if they scored 1.5 SD (standard deviation) below education-adjusted cutoff values on each individual test.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of CIND was determined by clinical judgment and was defined as, no loss of independence in daily activities, and impairment in at least one domain of the neuropsychological test battery. Participants were considered to have failed a test if they scored 1.5 SD below the education-adjusted cut-off values of each test [28]. Failure in at least half of the tests in each domain was considered as impairment in that domain.…”
Section: Participantsmentioning
confidence: 99%
“…The images were first visually assessed on the reconstruction images, and the final decision on stenosis (>50%) was made on the source images. 18 3. Lacunes were defined as lesions, 3 to 15 mm in diameter, with low signal on T1-weighted image and fluid attenuated inversion recovery, a high signal on T2-weighted image, and a hyperintense rim with a center following cerebrospinal fluid intensity on fluid attenuated inversion recovery.…”
Section: Neuroimaging Protocolmentioning
confidence: 99%